Rates of CO₂ registration taxes levied on passenger cars in the EU: Can they cause distortion? - Petr David (European Financial and Accounting Journal, 2020)
Some of the European Union member states try to tackle the issue of CO2 emissions generated by the transport sector through environmental registration taxes. The aim of the present research is to ascertain whether they use distorting and unfair parameters represented, in particular, by graduated progressive rates. Tax parameters consisting of average and marginal rates, taxes or nominal rates for 26,100 cases are calculated for various CO2 emission levels in passenger cars. We determine the optimal shape of such parameters from the point of grades, shape and progression and we identify differences from the optimum in the monitored countries. It was discovered that from the 13 countries of the European Union that use vehicle registration tax on passenger cars based on CO2 emissions, only Austria applies a tax that approximates the optimum. In five countries, we identified imperfections consisting of the graduated nature or local or global decrease in the rates examined. Registration taxes in the remaining countries are basically incompatible with the requirement of non-distortion. Even those taxes that do not generate significant revenues and are less socially sensitive, as is the case with the environmental registration tax, must be designed in a manner that is fair and non-distorting.
Keywords: H21; H23; 650; Registration Tax; CO2 Emissions; Distortion; Graduated Progression